1983
DOI: 10.1152/ajpregu.1983.245.2.r160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on cardiorespiratory function in the horse

Abstract: The effects of 5- and 10-wk treadmill exercise training on cardiorespiratory function were evaluated in the horse. Cardiac output (Q), heart rate (HR), and stroke volume (SV), as well as left ventricular (LVP), aortic (AoP), and mean right atrial (RAP) pressures and the peak first time derivative of LVP (LV dP/dtmax), were measured at rest and at five different levels of exercise up to 90% of initial predicted maximal HR (HRmax). Oxygen uptake (VO2) and respiratory exchange ratio (R) were also obtained under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
4
11
0
2
Order By: Relevance
“…However, the use of Cr did not influence the HR values. These results are similar to those observed by Thomas et al (1983), who verified that, in rest, HR does not differ after training. Similarly, Evans (1994) affirmed that, in the equine at rest, HR does not usually decrease with training, as observed for human beings.…”
Section: Resultssupporting
confidence: 92%
“…However, the use of Cr did not influence the HR values. These results are similar to those observed by Thomas et al (1983), who verified that, in rest, HR does not differ after training. Similarly, Evans (1994) affirmed that, in the equine at rest, HR does not usually decrease with training, as observed for human beings.…”
Section: Resultssupporting
confidence: 92%
“…THE ability of equine skeletal muscle to accommodate changes in demand associated with training has been demonstrated during the last decade. Most studies have focussed attention on the changes in muscle composition of either Standardbred Trotters (Lindholm and Piehl 1974; EssCn, Lindholm and Thornton 1980; Taylor and Brassard 1981; EssCn-Gustavsson er a1 1983 ;Henckel 1983a) or Thoroughbreds and/or Heavy Hunters (Guy and Snow 1977a, b;Snow and Guy 1979; Nimmo, Snow and Munro 1982 Thomas and Fregin 1981; Thornton er al 1983), whereas others have examined the cardiovascular (Bayly, Gabel and Barr 1983) and cardiorespiratory (Thomas, Fregin, Gerber and Ailes 1983) responses of horses subjected to submaximal treadmill training programmes. However, there appear to be no reports of the changes occurring in equine skeletal muscle as a result of treadmill training.…”
Section: Introductionmentioning
confidence: 99%
“…According to Thomas et al (1983), heart rate during submaximal exercise usually decreases by 10 to 20 bpm after conditioning. The present study found a mean overall reduction of 11 bpm in HR between Test 1 (110 bpm) and Test 2 (99 bpm), while the latter was very close to the average of Test 3 (100 bpm).…”
Section: Discussionmentioning
confidence: 99%